SQL queries for mere mortals : a hands-on guide to data manipulation in SQL - Viescas, John L., 1947- (For mere mortals series., 2018)
This book on generic SQL can be used by new users to learn the foundations of SQL or act as a reference for more experienced users. This new edition brings the content up-to-date with the latest versions of the major proprietary database systems, including Access, Oracle and MySQL.